Labdanum Resin from Cistus ladanifer L.: A Natural and Sustainable Ingredient for Skin Care Cosmetics with Relevant Cosmeceutical Bioactivities - David F. Frazão; Carlos Martins-Gomes; Jan L. Steck; Judith Keller; Fernanda Delgado; José C. Gonçalves; Mirko Bunzel; Cristina M. B. S. Pintado; Teresa Sosa Díaz; Amélia M. Silva (Plants, 2022)
Labdanum resin from Cistus ladanifer L. (Cistaceae) is an abundant natural resource in the Iberian Peninsula worth being explored in a sustainable manner. It is already used in the cosmetic industry; mainly by the fragrances/perfumery sector. However, given the highest market share and traditional uses, labdanum resin also has the potential to be used and valued as a cosmetic ingredient for skincare. Aiming to evaluate this potential, labdanum methanolic absolute and fractions purified by column chromatography were characterized by UPLC-DAD-ESI-MS and then evaluated for UV-protection, antioxidant, anti-elastase, anti-inflammatory, and antimicrobial activities. Labdanum absolute represented ~70% of the resin; diterpenoid and flavonoid fractions represented ~75% and 15% of the absolute, respectively. Labdane-type diterpenoids and methylated flavonoids were the main compounds in labdanum absolute and in diterpenoid and flavonoid fractions, respectively. Labdanum absolute showed a spectrophotometric sun protection factor (SPF) near 5, which is mainly due to flavonoids, as the flavonoids’ SPF was 13. Low antioxidant activity was observed, with ABTS radical scavenging being the most significant (0.142 ± 0.017, 0.379 ± 0.039 and 0.010 ± 0.003 mgTE/mgExt, for the absolute and flavonoid and terpene fractions, respectively). Anti-aging and anti-inflammatory activity are reported here for the first time, by the inhibition of elastase activity (22% and 13%, by absolute and flavonoid extract at 1 mg/mL), and by the inhibition of nitric oxide production in LPS-induced RAW 264.7 cells (84% to 98%, at 15 µg/mL extracts, flavonoid fraction the most active), respectively. Antimicrobial activity, against relevant skin and cosmetic product microorganisms, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, and Escherichia coli, revealed that only S. aureus was susceptible to labdanum absolute (MIC: 1.2 mg/mL) and its fractions (MIC: <0.3 mg/mL). In conclusion, labdanum resin showed potential to be used in sunscreen cosmetics, anti-inflammatory skincare cosmeceuticals or medicines but has low potential as a cosmetic product preservative given the low antioxidant and low-spectrum antimicrobial activities.